A study of postnatal foot length to determine gestational maturity in neonates - Shukla, Omprakash S.; Rathva, Jagruti J. (International Journal of Contemporary Pediatrics, 2020)
Background: Gestational age is a major determinant of newborn prognosis. Early identification of gestational age is a major priority to reduce global mortality from preterm birth. Therefore this study was conducted with an aim to find out an alternate simple, low cost and reliable method to identify accurate gestational ages. Methods: The cross sectional study was carried out at Rukmani Chainani Maternity and Neonatal Unit, SSGH and Medical College, Baroda from December 2019 to May 2020. Total 500 live newborns of different gestational ages within 72 hrs of birth which were appropriate for gestational age were enrolled in this study. Foot length, head circumference, crown heel length and weight were measured. Gestational age was estimated by antenatal USG, Ballard scoring and LMP. Correlation of foot length to gestational age and other anthropometric variables was done. Results: There was statistically significant positive correlation found between foot length and gestational age (correlation coefficient of 0.944 and p value of <0.0001). There was also positive correlation found between foot length and weight, head circumference and length with correlation coefficient of 0.942, 0.888 and 0.906, respectively. Using ROC curve, foot length cut-off value of 7.2 cm can be used for identifying preterm babies with sensitivity of 94.4% and specificity of 95.6%. Regression equation for gestational age calculation was GA=6.669+4.0601[FL]. Conclusions: This study had demonstrated that Foot length is a simple and reliable anthropometric measurement to assess gestational age and to screen prematurity.